Роль переговорів в процесі надання консалтингових послуг - Серських, Надія Сергіївна; Серских, Надежда Сергеевна; Serskykh, Nadiia (My University, 2018)
UK: Проаналізовано теоретичні підходи до трактування поняття «консалтинг», «консалтингова послуга», «консалтинг в агросервісі». Розглянуто основні етапи переговорного процесу між консультантами та споживачами консалтингових послуг. Запропоновано таблицю самодіагностики консультантів в перегово-рному процесі та модель «Квадрантів взаємодії» консультанта та клієнта. Визначено можливі стратегії консультантів в переговорному процесі. EN: The wording of Article purposes. The purpose of the paper is to analyze the theoretical approaches to the definition of the concept of "consulting", "consulting-service" and to determine the role of negotiation when establishing the rela-tionship between the pro-wider consulting services and its client. The theoretical approaches to the interpretation of the concept "consulting", "consulting service", "consulting in ag-roservice" are analyzed. The main stages of the negotiation process between consultants and consumers of consulting services are considered. The table of self-diagnostics of consultants in the negotiation process and the model of the “In-teraction quadrant” of the consultant and client are offered. The possible strategies of consultants in the negotiation process are determined.
The role of negotiation in consulting services
Keywords: консалтинг; консалтингова послуга; консалтингова послуга в агросервісні; переговори; етапи переговорів; стратегії переговорів; consulting; consulting service; consulting service in agro-services; negotiations; negotiation stages; negotiation strategies